Cone-beam computerized tomography as a novel noninvasive method to determine the palatal grafts thickness - Prabhati Gupta; Suhail M Jan; Roobal Behal (Wolters Kluwer Medknow Publications, 2014)
Aim: The aim of this study was to apply a novel noninvasive method to obtain high quality images by cone-beam computerized tomography (CBCT) that consistently allowed the determination of the dimensions of palatal masticatory mucosa, which is the main donor area for soft tissue and connective tissue grafts used in periodontics, implant dentistry, and oral surgery. Materials and Methods: A total of 20 patients requiring palatal surgery participated. Thickness of the palatal tissue was measured at various points radiographically. At the time of the CBCT scanning, the patients wore acrylic measurement stent guides with radio-opaque markers at the measurement points. Results: The average thickness of the palatal mucosa was 2.96 mm in the canine area, 3.55 mm at the first premolar, 3.92 mm at the second premolar and 3.20 mm at the first molar. Statistically significant differences were observed as the distance from the gingival margin increased and the tissue over the premolars was found to be thicker than the other teeth. Conclusion: Cone-beam computerized tomography can be used as a noninvasive method accurately and consistently to determine the soft tissue thickness of the palatal masticatory mucosa at different locations on the palate.